2023
DOI: 10.1002/elps.202300035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasmid DNA isoforms on preparative anion exchange chromatography

Špela Kralj,
Špela Meta Kodermac,
Ines Bergoč
et al.

Abstract: Increased need for plasmid DNA (pDNA) with sizes above 10 kbp (large pDNA) in gene therapy and vaccination brings the need for its large‐scale production with high purity. Chromatographic purification of large pDNA is often challenging due to low process yields and column clogging, especially using anion‐exchanging columns. The goal of our investigation was to evaluate the mass balance and pDNA isoform composition at column outlet for plasmids of different sizes in combination with weak anion exchange (AEX) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A part of the published manuscripts was also presented at the last Monolith Summer Symposium that was held last year in Portorož, Slovenia. As a logical consequence of the spirit of this time, the topics of most papers that are summarized here are dealing with purification of nanoparticles like viruses [1][2][3], plasmid DNA isoforms [4,5] and RNA drug substances [6]. As is well known, monolithic stationary phases (including membranes) were firstly developed for fast separation of proteins [7], but only the last manuscript in this issue reports the development of a new monolithic stationary phase for protein separation [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A part of the published manuscripts was also presented at the last Monolith Summer Symposium that was held last year in Portorož, Slovenia. As a logical consequence of the spirit of this time, the topics of most papers that are summarized here are dealing with purification of nanoparticles like viruses [1][2][3], plasmid DNA isoforms [4,5] and RNA drug substances [6]. As is well known, monolithic stationary phases (including membranes) were firstly developed for fast separation of proteins [7], but only the last manuscript in this issue reports the development of a new monolithic stationary phase for protein separation [8].…”
Section: Introductionmentioning
confidence: 99%
“…The next three papers are dedicated to fractionation of materials containing different DNA and RNA forms [4][5][6]. Kralj et al reported the optimization of production of large plasmid DNA isoforms with sizes over 10 kbp using anion exchange monoliths.…”
Section: Introductionmentioning
confidence: 99%